The use of PCA, FA, CA for the evaluation of vegetable juices processed by lactic acid fermentation - J. Karovičová; Z. Kohajdová (Czech Journal of Food Sciences, 2002)
The cabbage-carrot juices were inoculated with Lactobacillus plantarum 92H at the concentration of 8 × 106 CFU/ml and fermented in a thermostat at 24°C for 150 hours. During the fermentation, both analytical (pH, total acidity, reducing sugars, l-ascorbic acid, lactic, acetic and citric acids, biogenic amines) and sensory (appearance, colour, turbidity, sediment and taste) parameters were followed. For the evaluation of the results of the chemical and sensory (taste) analyses of these juices the multivariate statistical methods were applied. PCA and FA reduced the 7 original analytical variables to 1 independent component (factor) that accounted for 96.92% of the total variance, and CA divided samples into 2 groups according to the contents of lactic and acetic acids. PCA and FA reduced the 8 taste and mixture taste descriptors to 2 components (factors) that accounted for 97.28% of the total variance.